God, Struggle, and Suffering in the Evolution of Life - Southgate, Christopher; Fiddes, Paul S.; Lloyd, Michael; Messer, Neil; Sollereder, Bethany; Wynn, Mark R. (Bloomsbury Publishing (UK), 2026)
This open access book stems from a unique set of conversations between six scholars concerned with the theological problem of suffering in the non-human world over millions of years . How is the confession of the Christian God compatible with all the struggle, violence and suffering to which the Darwinian world testifies? This work identifies key fault lines in this rapidly growing debate - over the questions of resistance to the divine will in the non-human creation in particular. Is the picture of the biological world we derive from the sciences indicative of a profound resistance, distorting the character of creation? If so, what is the origin and character of this resistance? Or is it unnecessary to postulate such resistance before the evolution of human beings and their sin? Or is an intermediate position, in which some specific characteristics hint at resistance, the most coherent approach? Six leading academic press on this question in a way that illustrates the quality of the conversation we have been able to achieve in our colloquia. As such it also provides a model for how theology can be done collaboratively, respecting diversity of positions and using that diversity to advance the frontiers of debate. The eBook editions of this book are available open access under a CC BY-NC-ND 4.0 license on bloomsburycollections.com. Open Access was funded by the University of Exeter, Baylor University, and Wycliffe Hall, Oxford.